Complete and incomplete Kawasaki disease: Clinical differences and coronary artery outcome from a national prospective surveillance study in Switzerland - S. Bressieux-Degueldre; E. Gradoux; S. Di Bernardo; N. Sekarski (Frontiers Media S.A., 2023)
IntroductionThe aim of this national prospective surveillance study was to compare the clinical presentation, laboratory findings, treatment, and coronary artery outcome in patients with incomplete and complete Kawasaki disease (KD).MethodsBetween March 2013 and February 2019, children with a diagnosis of complete and incomplete KD were reported by the Swiss Paediatric Surveillance Unit and prospectively enrolled. Clinical data, laboratory values, treatment, and echocardiographic features were collected at diagnosis and 1 year of follow-up. Data were compared between children with complete or incomplete KD.ResultsA total of 351 questionnaires were registered from children with a diagnosis of KD. Of them, 219 (62.4%) children had complete KD, and 132 (37.6%) children had incomplete KD. Children with incomplete KD were younger and had a longer-lasting fever; however, there were no differences in the level of C-reactive protein. All but four children received intravenous immunoglobulin treatment, whereas 14% of children were treated with corticosteroids. Children with incomplete KD were more often treated with corticosteroids than children with incomplete KD (p = 0.01). At diagnosis, 39 (11.1%) patients had only coronary artery dilation and 57 (16.2%) had at least one coronary artery aneurysm. There were no differences in coronary artery involvement between the two groups. At follow-up, 273 of 294 (92.8%) patients had no coronary artery involvement, with no difference between the two groups (p = 0.609). The overall incidence of coronary artery aneurysms at diagnosis was 16.2%. At follow-up, most coronary artery aneurysms had regressed, and coronary artery aneurysms were present in only 5.8% of the patients. Coronary artery aneurysms were slightly more frequent in patients with incomplete KD at follow-up (p = 0.039) but not at diagnosis (p = 0.208).ConclusionAlthough the clinical presentation in children with incomplete and complete KD differs, the absence of coronary artery involvement does not. The use of corticosteroids appears to be preventive against the development of coronary artery aneurysms in these patients. However, the results of this study suggest a lower rate of coronary artery aneurysm regression in patients with incomplete KD. Further studies on a larger scale are needed to assess the risk of non-regression of coronary artery aneurysms in this particular group of patients.